Možnosti ve vytápění rodinného domu - Kovács, David (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2025)
Bakalářská práce se věnuje návrhu tepelných zdrojů pro ohřev vody a vytápění v rodinném domě. Práce se skládá ze čtyř jednotlivých částí, kdy první část se skládá z popisu možností ve vytápění rodinného domu. Druhá část se zaobírá výpočtem tepelných ztrát objektu a určení návrhového tepelného výkonu. Ve třetí části se nachází výpočet roční potřeby tepla pro vytápění a ohřev teplé užitkové vody spolu s návrhem jednotlivých zdrojů tepla. V poslední části je provedeno ekonomické zhodnocení zvolených zdrojů z pohledu nákladů na provoz.

The bachelor's thesis deals with the design of heat sources for water heating and heating in a family house. The thesis consists of four individual parts, where the first part consists of a description of options for heating a family house. The second part deals with calculation of heat loss of the building and determination of the design heat output. The third part contains calculation of annual heat demand for heating and domestic hot water together with the design of individual heat sources. In the last part, an economic evaluation of the selected sources in terms of operating costs is carried out.
Possibilities in heating family houses
Keywords: Tepelné ztráty; tepelné zdroje; vytápění; ohřev vody; náklady na vytápění; Heat loss; heat sources; heating; water heating; heating costs